Pengaruh Inflasi dan Suku Bunga terhadap Rasio Profitabilitas pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Amalia Nur Azizah; Elmira Siska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of inflation and interest rates on banking profitability as measured through Return on Assets (ROA) in conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research was conducted from April to May 2025 with a quantitative approach and multiple linear regression analysis methods. The data used are secondary data obtained from the annual financial statements of eight conventional banks as well as macroeconomic data from Bank Indonesia, which were selected through the purposive sampling method. The data analysis process includes descriptive statistics, classical assumption test, t test, F test, and determination coefficient. The results of the study show that partially, neither inflation nor interest rates have a significant effect on ROA. This is shown by the value of t calculating inflation of 0.049 < t table 2.02619 with a significance of 0.961 > 0.05, and t calculating interest rates of 1.163 < t table 2.02619 with a significance of 0.252 > 0.05. However, simultaneously, inflation and interest rates have a significant effect on ROA, as shown by the calculated F value of 8.698 > F table 3.25 and the significance of 0.001 < 0.05. These findings indicate that although individual macroeconomic variables do not have a significant impact, together they have an influence on banking profitability. This research contributes to policy makers and banking industry players in understanding macroeconomic dynamics on banks' financial performance.